Insomnia severity and its relationship with demographics, pain features, anxiety, and depression in older adults with and without pain: cross-sectional population-based results from the PainS65+ cohort - Dragioti, Elena (Ann Gen Psychiatry, 2017)
BACKGROUND: Insomnia is a major cause of concern in the elderly with and without pain. This study set out to examine the insomnia and its correlates in a large sample of community adults aged ≥65 years. METHODS: A cross-sectional postal survey was completed by 6205 older individuals (53.8% women; mean age = 76.2 years; SD = 7.5). The participants also completed the Insomnia Severity Index (ISI) and questionnaires assessing pain intensity, pain spreading, anxiety, depression, and basic demographic information. The sample was divided into three groups based on the presence and duration of pain: chronic pain (CP; n = 2790), subacute pain (SP; n = 510), and no pain (NP; n = 2905). RESULTS: A proportion of each of the groups had an ISI score of 15 or greater (i.e., clinical insomnia): CP = 24.6%; SP = 21.3%; and NP = 13.0%. The average scores of ISI differed significantly among CP, SP, and NP groups (p < 0.001). Stratified regression analyses showed that pain intensity, pain spreading, anxiety, and depression were independently related to insomnia in the CP group. Anxiety and depression were independently related to insomnia in the SP group, but only anxiety was significantly associated with insomnia in the NP group. Age and sex were not associated with insomnia. CONCLUSIONS: This study confirms that insomnia is not associated with chronological aging per se within the elderly population. Although the possible associations of insomnia with pain are complex, ensuing from pain intensity, pain spreading, anxiety, and depression, our results highlighted that anxiety was more strongly associated with insomnia in all groups than the depression and pain characteristics. Therapeutic plans should consider these relations during the course of pain, and a comprehensive assessment including both pain and psychological features is essential when older people are seeking primary health care for insomnia complaints.